The significance of the door in nursing homes: a symbol of control in the domestic sphere - Kaup, Migette L. (My University, 2011)
This article explores how public/private contradictions can be enacted in the space of the nursing home through the use of architectural features that signal transition and passage, most specifically the door. To explore these relationships, two alternative forms of the institutionalized skilled care setting will be described. The first represents the state of the most common form of nursing home, the institution that has been patterned after a hospital; the second represents an emerging place type in long-term care called a "household," patterned after the domestic home. The divergent spatial experiences of these settings will be expressed through the role of the door and the supporting transitional features that are architecturally determined and will compare and contrast the dramatic changes that can occur in the ideological communication of these domains. Their use, their language, and therefore their meaning within the spaces are suggested through the patterns of behavior they support.
Keywords: Nursing homes; Public / private dichotomy; Doors; Institution; Meanings of home